Teaching technology foresight to business and management students - McGowan, Phill (IATED Academy, 2022)
Predicting the future is an important, yet highly difficult management task. Disruptive technologies create new ways of working, shopping, and consuming, offering both risk and opportunity. Leading experts struggle to make accurate predictions about which technology will become ubiquitous, and which will face obscurity. However, 82% of jobs require digital skills, and while the current skillset is known, future requirements are unknown. Therefore, developing the ability of students to understand and capitalise on technology change is a problematic, but worthwhile endeavour.